THE EFFECT OF COUNTRY IMAGE, COMPANY IMAGE, BRAND IMAGE, MEDIATED BY BRAND ATTITUDE ON BUYING INTENTIONS OF WULING AND DFSK BRAND IN SURABAYA - Reizano Amri Rasyid; Azmil Chusnaini; C Candraningrat; Mochammad Irfan Yusuf (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to examine and investigate the effects of the Chinese automotive product brand on the Indonesian market. Based on the literature relating to the image of the country and the influence of the country of origin, a research model was developed to evaluate the image of the country, the image of the company and the image of the brand. To test models and investigate the influence of country, company and brand image on brand attitudes and purchase intentions, investigate the influence of country, company and brand image on brand attitudes and purchase intentions. State image consists of four dimensions: political image, economic image, citizen image and image of state relations. This research is expected to provide information and theoretical evidence for research on China's image, especially regarding Wuling and DFSK brand products, and also provide empirical evidence to support the